2000
DOI: 10.1063/1.1287064
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional three-body problem via symbolic dynamics

Abstract: Symbolic dynamics is applied to the one-dimensional three-body problem with equal masses. The sequence of binary collisions along an orbit is expressed as a symbol sequence of two symbols. Based on the time reversibility of the problem and numerical data, inadmissible (i.e., unrealizable) sequences of collisions are systematically found. A graph for the transitions among various regions in the Poincare section is constructed. This graph is used to find an infinite number of periodic sequences, which implies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…As established for celestial problem (Tanikawa and Mikkola, 2000), the following properties are also true for our Coulomb system: Property 4.1: A trajectory in the (Q 1 , Q 2 )-plane transversely crosses the line Q 1 = Q 2 except at (θ, R) = (0, 0), if it does at all. Property 4.2: If a trajectory crosses the line Q 1 = Q 2 on the (Q 1 , Q 2 )-plane, a double collision occurs before the trajectory again crosses it.…”
Section: Symbolic Dynamicsmentioning
confidence: 97%
See 4 more Smart Citations
“…As established for celestial problem (Tanikawa and Mikkola, 2000), the following properties are also true for our Coulomb system: Property 4.1: A trajectory in the (Q 1 , Q 2 )-plane transversely crosses the line Q 1 = Q 2 except at (θ, R) = (0, 0), if it does at all. Property 4.2: If a trajectory crosses the line Q 1 = Q 2 on the (Q 1 , Q 2 )-plane, a double collision occurs before the trajectory again crosses it.…”
Section: Symbolic Dynamicsmentioning
confidence: 97%
“…Our numerical calculation up to the word length 15 showed that the inadmissible words are only the words including the words 1122 and 2211. Note that 1122 and 2211 are also inadmissible words for the celestial problem(the case of (Z, ξ) = (−1, 1)) and other inadmissible words exist (Tanikawa and Mikkola, 2000). On the other hand, for the case of the helium (Fig.6), i.e., large ξ, there is no torus.…”
Section: Symbolic Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations